Understanding the Lean Enterprise: Strategies, Methodologies, and Principles for a More Responsive Organization - Andrea Chiarini; Pauline Found; Nicholas Rich (Switzerland Springer, 2016)
This publication is in collaboration with the University of Buckingham and is the result of a combined research and review process carried out by the three Editors who belongs to the University of Ferrara, Italy, the University of Buckingham, UK and Swansea University, UK. The book deepens the debate about the lean enterprise from both an academic and a professional management perspective. It thus provides the reader with a sound understanding of the modern lean enterprise and its current evolution. A range of innovative topics are covered, with individual chapters addressing the combinations of lean with hoshin kanri, green management, IT, organizational learning, flow accounting, system thinking, problem solving, internationalization aspects, luxury industry, and product innovation. Since the term "lean" first entered contemporary operations management language in 1990 to describe a set of practices proven to deliver superior performance over mass production systems, the lean approach to waste reduction and value generation has moved from vehicle production to other manufacturing sectors. It has reshaped the support functions of manufacturing businesses and has evolved from private industry into the public sector. Lean thinking is now a dominant model of operations management and has brought with it a new language and toolbox.
Keywords: Business enterprises; (UGB-253) Management accounting for business